2016
DOI: 10.1299/mej.15-00682
|View full text |Cite
|
Sign up to set email alerts
|

Development of failure evaluation method for BWR Lower head in severe accident; - Creep damage evaluation based on thermal-hydraulics and structural analyses -

Abstract: In existing severe accident codes such as MELCOR and THALES2, rupture of reactor pressure vessel (RPV) by relocated molten core is judged using simple models such as temperature and/or stress criteria. However, it is difficult to assess rupture behavior of the lower head of RPV in boiling-water-type nuclear power plants due to severe accident like Fukushima Daiichi. One reason is that boiling water reactors (BWRs) have geometrically complicated structure with a lot of penetrations. Another one is that BWR lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…To assess progress of severe accident and to predict rupture time and location of reactors due to severe accident, Katsuyama et al (2016) developed finite element model of RPV lower head including, penetrations, and welds, and four types of creep damage failure evaluation methods of Kachanov and LMP criterions confirmed in this study. Through the analyses, it was shown that failure occurred only near the penetrations under simulated conditions.…”
Section: Creep Analysis and Creep Damage Evaluationmentioning
confidence: 99%
“…To assess progress of severe accident and to predict rupture time and location of reactors due to severe accident, Katsuyama et al (2016) developed finite element model of RPV lower head including, penetrations, and welds, and four types of creep damage failure evaluation methods of Kachanov and LMP criterions confirmed in this study. Through the analyses, it was shown that failure occurred only near the penetrations under simulated conditions.…”
Section: Creep Analysis and Creep Damage Evaluationmentioning
confidence: 99%
“…Recently, some interesting attempts to simulate numerically specific NSA scenarios have been done [11,47,38,48,70]. In [71] the relocation of molten materials in nuclear reactors was modeled using a thermo-coupled Volume of Fluid (VOF) method [30], while in [10] the flow and solidification of molten core debris was studied with the Moving Particle Semi-implicit (MPS) method [41].…”
Section: Introductionmentioning
confidence: 99%